Enhancing Local Government Civil Servant Quality Through Continuous Education And Training: A Literature Review - Muhammad Wahyu Prasetyo Adi (Jurnal Honai, 2026)
The phenomenon of policies not being fully implemented has raised serious questions about the government’s effectiveness. This practice is particularly noteworthy when the application of justifications during annual evaluations fails to yield optimal results. The recurrence of old patterns, coupled with unexpected dynamics, forces implementation to halt, restart, or remain unfulfilled. Enhancing understanding through education and training is the simplest tool for steering a practical and adaptive course at a time when efficiency is being enforced nationwide. This study employs a qualitative approach in the form of a literature review. Data were drawn from scientific research, limited to case studies from the past five years. The data were analyzed using thematic analysis; the primary reasons for flexibility and accessibility given that the findings were constrained by the study’s focus were relatively well-defined, allowing different findings, terminology, and patterns to be integrated into appropriate themes. The results of this study highlight two relatively straightforward key agendas. First, establishing continuous education a process that fosters a comprehensive understanding divided into three patterns: first, a pattern of thinking; second, a pattern of understanding; and third, a pattern of behavior. These three patterns are integrated into the implementation of continuous education. Second, it establishes continuous training through five approaches: On-the-Job Training, Leadership Development, Coaching and Mentoring, E-Learning and Microlearning, and Soft Skills Training. These two key aspects education and training have implications based on the capacity of public organizations and the needs to be developed.